2017
DOI: 10.1111/cbdd.13001
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of tyrosinase by 4H‐chromene analogs: Synthesis, kinetic studies, and computational analysis

Abstract: Inhibition of mushroom tyrosinase was observed with synthetic dihydropyrano[3,2-b]chromenediones. Among them, DHPC04 displayed the most potent tyrosinase inhibitory activity with a K value of 4 μm, comparable to the reference standard inhibitor kojic acid. A kinetic study suggested that these synthetic heterocyclic compounds behave as competitive inhibitors for the L-DOPA binding site of the enzyme. Furthermore, molecular modeling provided important insight into the mechanism of binding interactions with the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…The identified residues have been reported to be important for stabilizing the interactions of the derivatives with the active site [ 12 ]. Furthermore, the formation of hydrogen bonds with the residues Met215, Asn205, and Glu195 have been shown to be relevant for the molecular recognition and stabilization of the interactions with the binding pocket [ 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The identified residues have been reported to be important for stabilizing the interactions of the derivatives with the active site [ 12 ]. Furthermore, the formation of hydrogen bonds with the residues Met215, Asn205, and Glu195 have been shown to be relevant for the molecular recognition and stabilization of the interactions with the binding pocket [ 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…The molecular docking results showed that the KA derivatives [ 65 ] have a high conformational selectivity to the tyrosinase when compared with kojic acid, mainly due to the presence of a substituted phenyl group, which formed new interactions with the residues of the binding pocket. All derivatives showed favorable interactions that are consistent with the chelation of copper ions (Cu-A and Cu-B) ( Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The interaction mode of the various pigments into the binding pockets of mTYR and hTYRP1 was also assessed by a molecular docking study. This computational technique has been successfully used to predict the binding of potential inhibitors to tyrosinase en zymes [38][39][40][41][42]. To validate the docking protocol, the crystallographic inhibitor tropolone was re-docked.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…This residue corresponds to Asn364 of TYR and interacts with KA and CA in a similar manner. Val283 has been discussed before to form π–π stacking interactions with ligands [ 49 , 56 ], and this is also true for Val377 in TYR. Other similar interactions can be noticed for Phe90, Ala287, and Phe292 of abTYR and Phe207, Ser380, and Phe386 of TYR ( Figure S5 ).…”
Section: Resultsmentioning
confidence: 99%